To what the people attribute their recovery from PTSD: Qualitative analysis of long-term war-related cases - Ajduković, Dean; Bogić, Marija (2009)
The qualitative analysis of 20 in-depth interviews with people with ongoing PTSD and the recovered from PTSD aimed to identify mechanisms to which they attribute improvement in mental health. The sample included refugees in Italy, IDPs and returnees in Bosnia Herzegovina and Croatia, with equal number of male and female interviewees ; 12 with past PTSD and 8 with current PTSD as assessed by the MINI International Neuropsychiatric Interview. Both groups felt similarly and substantially changed from before the war (e.g. less sociable, preferred being alone, highly emotional, irritable, restless, bitter, angry, distrustful, having nightmares). The recovered participants reported more often feeling stronger than before the war, more psychologically mature, better relationships within family, increased interest for other people, more hopeful. For them most helpful was: strong and continuous support from the partner and family members, having a job, different kinds of financial support, family reunion, ability to care for children. They more often attributed recovery to own personality characteristics. Both groups attributed recovery also to the professional help, but it seems that the recovery from PTSD is more often attributed to resilience and natural support systems that to the professional help.
Projekt MZOS
ENG